Assessment tool to identify the effects of COVID-19 on food security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The survey has been successfully developed and has been applied during 2020 in Climate-Smart Villages (CSV) and some territories where have LTACs work.